Recent Trends and Long-Run Prospects for Female Earnings - Fuchs, Victor R. (American Economic Review, 1974)
This paper discusses the recent behavior of the female-male earnings differential and asks how it is likely to change in the future.' After adjusting for hours, age and schooling, we find that, contrary to results obtained in other studies from unadjusted data, the female-male earnings ratio among whites increased between 1959 and 1969 by 4.8 percent despite an unprecedented increase in the female-male employment ratio among whites of almost 20 percent in the same decade-a favorable augury for future trends in the earnings ratio. The data used below come from the 1/1000 sample of the 1960 and 1970 Censuses of Population.2 Due to lack of time and space, I focus on the sex differential among whites. However, the color differential between blacks and whites narrowed appreciably between 1959 and 1969. Black female hourly earnings, adjusted for age and schooling, rose 82 percent compared with 68 percent for black males and 53 percent for white females. By 1969, hourly earnings of black females were only 15 percent less than those of white females of comparable age and schooling, while for women with more than twelve years of schooling the adjusted color differential had practically disappeared. Total earnings in 1959 (1969) are calculated for workers classified for a variety of characteristics; total annual hours are estimated by multiplying weeks worked in 1959 (1969) by hours worked in the census week in 1960 (1970) for each worker and summing across all the workers in a classification. Finally, total earnings are divided by total hours to obtain, for each classification, average hourly earnings-or, equivalently, the mean of individual average hourly earnings weighted by annual hours. I focus on hourly earnings as the best mea* Professor of economics, City University of New York, and Vice-President, Research, National Bureau of Economic Research (NBER). Work on this paper was begun while I was a Fellow at the Center for Advanced Study in the Behavioral Sciences, 1972-73, with partial support provided by the Russell Sage Foundation. It was continued at the NBER under a grant from the Rockefeller Foundation. Carol Breckner, Phyllis Goldberg, Jan Platt, and Christy Wilson provided research assistance and many useful suggestions; Charlotte Boschan wrote the earnings program; Robert Michael and Yoram Weiss made helpful comments on an earlier draft. I am grateful to all of the above; they bear no responsibility for the views expressed. In particular, this paper has not been submitted to the NBER Board of Directors for approval and is not an official NBER publication. I I do not consider determinants of the general level of earnings (female and male). 2 See Fuchs (1968) for a discussion of the strengths and shortcomings of this source, which provides much useful information on employed persons' sex, schooling, age, race, marital status, occupation, and industry. All persons who were at work during the census week and had earnings in the year preceding the census are included in the sample except agricultural, religious, and unpaid family workers, since, as is well known, the estimation of earnings and work hours for such workers is difficult.